Administration and distribution of testate and intestate estates in Peninsular Malaysia / Yusof Ali - Ali, Yusof (Faculty of Law, 1982)
Estates can be divided into two types namely testate and intestate. Testate refers to a person who died leaving a will and intestate means dying without a will. The law governing wills in this country is the Wills Ordinance, 1959. The duty of administering a deceased person's estate devolves on his personal representative who is called his "executor" if he has made a will or his "administrator" if he dies intestate. There are three types of estates administered, namely, estate of summary administration, small estate and ordinary estate. An estate of summary administration is one consisting wholly of movable property the value of which does not exceed $50,000 and where no petition for letters of administration is pending. The Official Administrator of the public Trustee Department is empowered to administer such an estate whether the deceased person has left a valid will or not. The distribution of a small estate is subject to the Small Estates (Distribution) Act, 1955. A small estate means an estate of a person who died intestate consisting wholly or partly of immovable property the total value of which does not exceed $50,000. An application for the distribution can be made, to the Collector of Land Revenue.